Emerging Socialities in 21st Century Healthcare - Hardon, Anita; Hadolt, Bernhard (Book collections on Project MUSE., 2020)
The landscape of healthcare is changing rapidly, both on an organisational and a technological level. This book gathers medical anthropologists to examine the ways that both patients and health care workers are being affected by new policies, market, and technologies. Contributors cover a wide range of topics, including vaccination, disability, migration, and self-medication, making clear that not only are changing circumstances leading to the emergence of new socialities, but they are also driving new ethics and moralities.